Sequence analysis of the 17-kilodalton-antigen gene from Rickettsia rickettsii. - Anderson, B E (1987)
DNA obtained from the Sheila Smith strain of Rickettsia rickettsii was digested to completion with the restriction endonucleases BamHI and SalI and ligated with the plasmid vector pUC19. The ligation mixture was used to transform Escherichia coli. A total of 465 bacterial clones were screened for antigen production with hyperimmune rabbit serum. One of the reactive clones, containing a recombinant plasmid designated pSS124, was solubilized and subjected to immunoblot analysis and revealed expression of a 17-kilodalton protein reactive with anti-R. rickettsii serum that comigrated with an antigen from R. rickettsii. A 1.6-kilobase PstI-BamHI fragment from pSS124 was subcloned and continued to direct synthesis of the 17-kilodalton antigen. The nucleotide sequence was determined for this 1.6-kilobase subclone, which encompassed the gene encoding the polypeptide as well as flanking regions containing potential regulatory sequences. The open reading frame consisted of 477 nucleotides that specified a 159-amino-acid protein with a calculated molecular weight of 16,840. The deduced amino acid sequence contained a hydrophobic sequence near the amino terminus that resembled signal peptides described for E. coli. The carboxy terminus was hydrophilic in nature and probably contained the exposed epitopes.